2014
DOI: 10.3390/w6123758
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Land Use Change Dynamics and Its Impacts on Hydrological Processes in the Jialing River Basin

Abstract: Land use changes are important aspects of global change and affect regional water cycles, environmental quality, biodiversity and terrestrial ecosystems. To understand the temporal and spatial land use change in the Jialing River Basin and its impacts on the hydrological cycle, land use change models and the variable infiltration capacity (VIC) model were applied separately to the Jialing River Basin. Real change and final change were analyzed to determine the consequences of land use changes and their hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
(38 reference statements)
0
28
0
Order By: Relevance
“…However, it is recognized that air temperature is one of most important factors influencing E 0 . As the range of the temperature change over the study period was not more than 2 • in this region (Zheng et al, 2010), and as Zhang et al (2014) found that the E 0 increased by only 1.16 mm per month for a temperature increase of 2 • in the Gulang River basin (next to the Heihe River basin), it was assumed that E 0 in the HRB was constant over the study period and the same as instrumented times. The term w is a catchment-scale model parameter determining the evaporation ratio (E/P ) for a given E 0 /P .…”
Section: Estimating E Based On Reconstructed Land Usementioning
confidence: 99%
“…However, it is recognized that air temperature is one of most important factors influencing E 0 . As the range of the temperature change over the study period was not more than 2 • in this region (Zheng et al, 2010), and as Zhang et al (2014) found that the E 0 increased by only 1.16 mm per month for a temperature increase of 2 • in the Gulang River basin (next to the Heihe River basin), it was assumed that E 0 in the HRB was constant over the study period and the same as instrumented times. The term w is a catchment-scale model parameter determining the evaporation ratio (E/P ) for a given E 0 /P .…”
Section: Estimating E Based On Reconstructed Land Usementioning
confidence: 99%
“…Anyway, the obvious finding is that the deforestation increases and reforestation decreases the annual flow. At the same time, deforestation increases flood peaks and volumes (Andréssian 2004), while forested catchments have greater infiltration rates, which may decrease catchment runoff (Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, previous studies showed that vegetation affects snow accumulation by interception and sublimation, and affects snowmelt by alerting the energy balance of land surface [64][65][66]. However, the relationship between snow and vegetation is highly variable and complicated, depending on climatic, topographic and vegetation conditions [65,67,68]; On the other hand, vegetation modifies runoff yield mainly by interception and ET [69,70]. The effects of land cover change on MCR cannot be evaluated since we adopted the constant land cover during the entire study period.…”
Section: Effects Of Climate and Land Cover Changesmentioning
confidence: 99%